A case study on palay seed production by Mrs. Rebecca Villamor Barbusa - Dilao, Ildefonso, Gacusan
This study described the palay seed production of Mrs. Rebecca Villamor Barbusa, who was once one of the most outstanding farmers of the year and twice an awardee as best palay seed grower.